Creating Website-based Documentation of Green Minak Pangalun as Traditional Medicine for Health Care (Talenta Publisher, 2022)
Green Minak Pangalun (GMP) or Karo Oil (massage oil) is a traditional oil made by the Karo Tribe which is mixed traditionally and is well known for its benefits and has been used for a long time among the people of North Sumatra. Website is part of the development of information technology that can be accessed by users widely. The research objective is to create website-based documentation of the benefits, materials, and methods of making GMP so that it can be used in the future. The research method used is descriptive research using a qualitative approach. This study uses observation techniques, in-depth interviews, informant approach and analysis to obtain the required data. This research will produce complete documentation related to the ingredients and methods of making GMP that can be used for health care and can be accessed through the website. With the documentation of GMP, it is hoped that the traditional medicinal concoction of the people of Tanah Karo, North Sumatra, can be sustainable and may be used in general for health care.